DEVELOPMENT OF QURAN PRINTING AND PRESERVATION: AN EDUCATIONAL PERSPECTIVE - Taufiq, Ahmad; Azly, Noor; Zainuddin, Nasaie (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This paper examines the historical and contemporary development of Quran printing and preservation. Tracing its evolution from early oral transmission and handwritten manuscripts to modern mechanised and digital production. The study highlights how the principles established during the time of the Prophet Muhammad. Accuracy, verification and standardisation. Continue to guide present-day Quran printing processes. Particular attention is given to Malaysia, where the Printing of Quranic Texts Act 1986 positions the Ministry of Home Affairs (KDN) as the sole authority responsible for licensing, approving and inspecting Quran printing activities. Using qualitative document analysis, the research synthesises historical records, manuscript traditions and regulatory documents to identify key strengths and challenges within the current system. Findings show that while Malaysia upholds strong regulatory control and adherence to rasm Uthmani, issues such as reliance on imported materials, workflow inconsistency and digital authentication remain significant. The study concludes that a more integrated optimisation framework is needed to align regulatory governance, technological capability and preservation ethics in ensuring the sustained accuracy, sanctity and accessibility of the Quran in the modern era.